MEDICAL DEVICE-RELATED PRESSURE INJURY: FREQUENCY AND ASSOCIATED FACTORS (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: to analyze the occurrence of pressure injuries related to medical devices in patients admitted to an intensive care unit. Method: quantitative, observational, descriptive, prospective cohort study, carried out with 171 patients, from May 15 to August 31, 2018 in the intensive care units of a public hospital in the Federal District. Results: the main risk factors were the presence of pressure injuries at admission, with a significant association for the formation of pressure injuries related to medical devices (p=0.002), and patients who progressed to death, with an association for the formation of pressure injuries related to medical devices (p=0.012); medical device-related pressure injury incidence rate of 40.35%. Conclusion: the use of medical devices has grown, as well as the appropriation of these technologies in the critical care environment. The multidisciplinary team should be aware of the formation of pressure injuries related to medical devices that can affect hospitalized patients.